2022
DOI: 10.1186/s13063-022-06566-5
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in the treatment of patients with severe COVID-19 (INFLIXCOVID): protocol for a randomised, controlled, multicentre, open-label phase II clinical study

Abstract: Background Despite the intense global research endeavour to improve the treatment of patients with COVID-19, the current therapy remains insufficient, resulting in persisting high mortality. Severe cases are characterised by a systemic inflammatory reaction driven by the release of pro-inflammatory cytokines such as IL-6 and tumour-necrosis-factor alpha (TNF-α). TNF-α-blocking therapies have proved beneficial in patients with chronic inflammatory diseases and could therefore pose a new treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…All the above conclusions are drawn from the meta-analysis of Tripathi et al [ 25 ] in adult patients with IBD and COVID-19, suggesting that the use of biologics leads to a favorable outcome due to reduction of cytokine storm. In line with this finding, a very recent protocol for a phase-2 randomized controlled trial for testing the efficacy and safety of infliximab in treating COVID-19 has been published [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the above conclusions are drawn from the meta-analysis of Tripathi et al [ 25 ] in adult patients with IBD and COVID-19, suggesting that the use of biologics leads to a favorable outcome due to reduction of cytokine storm. In line with this finding, a very recent protocol for a phase-2 randomized controlled trial for testing the efficacy and safety of infliximab in treating COVID-19 has been published [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data revealed that infliximab‐related delayed cutaneous hypersensitivity accounted for 83.33% in 0–30 days and 16.67% in 180–210 days, and adalimumab‐related delayed cutaneous hypersensitivity accounted for 31.82% in 0–30 days, and the others were evenly reported in the remaining stages, with a median of 166.5 days (interquartile range [IQR]: 18–889.5). Adalimumab at 40 mg was given as a single subcutaneous injection 19 and infliximab at 5/mg/kg body weight was given as a single subcutaneous injection according to the usual regimen of drug treatment 20 . Notably, delayed cutaneous hypersensitivity may occur after the first infliximab dosage for COVID‐19 treatment, whereas adalimumab showed a small peak after the first dose and more extensive distribution, which may be related to the different drug structure.…”
Section: Resultsmentioning
confidence: 99%
“…Adalimumab at 40 mg was given as a single subcutaneous injection 19 and infliximab at 5/mg/kg body weight was given as a single subcutaneous injection according to the usual regimen of drug treatment. 20 Notably, delayed cutaneous hypersensitivity may occur after the first infliximab dosage for COVID‐19 treatment, whereas adalimumab showed a small peak after the first dose and more extensive distribution, which may be related to the different drug structure. A statistically significant difference was found in the time to onset associated with delayed cutaneous hypersensitivity for COVID‐19 treatment in infliximab or adalimumab (Mann–Whitney U test, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that Infliximab exerts favorable impact in terms of lowering the mortality rate of SARS-CoV-2 infection. More studies on the effects of Infliximab on severe COVID-19 should be conducted [28].…”
Section: Discussionmentioning
confidence: 99%